Equivalent Electrical Model of an Inductor Excited by a Triangular Current Including Saturation - Gonzalez-Teodoro, Jorge Rafael; Romero-Cadaval, Enrique; Asensi, Rafael; Kindl, Vladimir (Communications - Scientific Letters of the University of Zilina, 2020)
A model for an equivalent electrical circuit designed for a ferrite (3C90) inductor usually used in power converters excited by a non-sinusoidal current appropriate for use in power electronics is proposed. This study, based on 3D finite element analysis, leads to significant precision advantages over 2D analysis for non-symmetric inductors. The frequency range of the analysis for the toroidal core was between 15 kHz and 1 GHz, with different levels of excitation in non-saturation and saturation status focusing on the power loss.
Keywords: ferrite inductors; 3D finite element analysis; power losses; saturation; hysteresis; eddy current losses; magnetization